(untitled) (Research, Society and Development, 2020)
In this work, we aim to analyze Laws No. 11,741 / 2008 and No. 11,788 / 2008 that regulate the offer of internship for students regularly enrolled in educational institutions, whether higher education or basic education, as well as observing the guidelines of the Curricular Guidelines Nationals of Basic Education on internship practices and the potential of factories as learning spaces, according to the work of Moisey M. Pistrak. This qualitative bibliographic study on the issues related to the internship discipline was imposed from our professional experience in the internship coordination of a Professional School in the State of Ceará when we tried to understand by which method the integral formation of the student would take place. According to the Guidelines, the internship discipline should be based on the structuring axes of high school (work, science, technology and culture) to ensure the integration between theory / practice and the consequent integral education of the student.